Thai novice nurses' lived experiences and perspectives of breastfeeding and human milk in the Neonatal Intensive Care Unit (NICU) - Tippawan Srichalerm; Cynthia S. Jacelon; Lindiwe Sibeko; Jumpee Granger; Carrie-Ellen Briere (BMC, 2024)
Abstract Background Breastfeeding and human milk have well-documented health benefits for newborn infants, particularly those who are sick. However, breastfeeding rates and human milk feeding among infants in neonatal intensive units (NICU) in Thailand are still low; thus, breastfeeding promotion and support are required for Thai mothers of premature infants. Newly graduated nurses can play a critical role within the healthcare support system and can have a significant impact on improving breastfeeding practices in the NICU. The objective of this study was to investigate the lived experiences and perspectives of Thai novice nurses on supporting breastfeeding and human milk feeding in the NICU. Methods The study was conducted between March 2021 and May 2022 at three medical centers in the central region of Thailand. This study employed a descriptive phenomenological approach to explore Thai novice nurses' experiences and perspectives on breastfeeding. Purposive sampling was used to invite Thai novice nurses who have work experience in providing breastfeeding support to NICU mothers and their infants to participate in online interviews using a video conference platform (Zoom). Semi-structured questions were used to interview study participants in their native language. Data were analyzed using Colaizzi's method of data analysis to identify emergent themes. Member checks, peer debriefing, and self-reflection were applied to ensure the validity and trustworthiness of the study results. Back-translation was also used as a quality and accuracy assurance. Results A total of thirteen novice nurses agreed to participate in the study. All were female, and their ages ranged from 21 to 24 years old at the time of the interview. The researchers identified five major themes related to the overall study objectives and research questions. They are: positive attitude toward breastfeeding and human milk, facing breastfeeding challenges at work, self-confidence rooted in experience, professional skill needs, and requiring further support. Conclusions Our results suggest that breastfeeding education plays a vital role in encouraging new nurses to provide breastfeeding support to mothers of preterm infants. Establishing breastfeeding support training and innovative learning strategies can be crucial in developing appropriate breastfeeding practice guidelines and policies to support Thai breastfeeding mothers in the NICU.